Crack detection on beams by time-frequency analysis of transient flexural waves - APOSTOLOUDIA, Anastasia; DOUKA, Evanthia; HADJILEONTIADIS, Leontios J.; REKANOS, Ioannis T.; TROCHIDIS, Athanasios (Archives of Acoustics, 2007)
A method for crack detection in beams by time-frequency analysis of flexural waves is described. Two different time-frequency representations, namely the continuous wavelet transform and the smoothed pseudo-Wigner distribution are employed. Simulated and measured flexural waves in a cracked beam are analysed and both the location and size of the crack are accurately determined. The location of the crack is estimated using the arrival time of reflected waves with different group velocities. The ratio of the reflected wave energy to the incident wave one is calculated and used as an indicator of the crack size. Wave experiments in a slender brass beam are in good agreement with predictions verifying the efficiency of the method. In view of the results obtained, the advantages and shortcomings of the time-frequency representations employed are presented and discussed.